Constructing Post‐Permeation Method to Fabricate Polymer/Nanocrystals Hybrid Solar Cells with PCE Exceeding 6%. Issue 11 (11th January 2017) - Du, Xiaohang; Zeng, Qingsen; Jin, Gan; Liu, Fangyuan; Ji, Tianjiao; Yue, Yuanyuan; Yang, Yi; Zhang, Hao; Yang, Bai
Abstract : A post‐permeation method is constructed for fabricating bulk‐heterojunction hybrid solar cells. Porous CdTe film is prepared by annealing the mixture solution of aqueous CdTe nanocrystals and cetyltrimethyl ammonium bromide, after which the post‐permeation of polymer is employed. By this method, kinds of polymers can be applied regardless of the intermiscibility with the nanoparticles. The inorganic nanocrystals and the polymer can be treated under respective optimized annealing temperatures, which can facilitate the growth of nanocrystals without damaging the polymers. A high power conversion efficiency of 6.36% in the polymer/nanocrystals hybrid solar cells is obtained via systematical optimization. Abstract : Polymer/nanocrystals hybrid solar cells are made by a post‐permeation method. By this method, various polymers can be applied regardless of the intermiscibility with the nanoparticles. The inorganic nanocrystal layer and the polymer layer can be treated under their optimized annealing temperatures, respectively. A high power conversion efficiency of 6.36% in polymer/nanocrystals hybrid solar cells is achieved.